Singing Alexandria : music between practice and textual transmission - Prauscello, L. (Mnemosyne, Supplements, 2006)
This volume investigates the transmission and ancient reception of ancient Greek texts with musical notation. It provides a reconstruction of the dynamics of reception orienting the re-use and re-shaping of musical and poetic tradition in the entertainment culture of the post-classical Greek world. The study makes full use of literary, papyrological and epigraphic evidence, and in particular includes a detailed philological analysis of surviving musical papyri and of their relationship to the editorial activity of Alexandrian scholarship. The study helps to relocate musical documents in the world of their production and reception.